Determinants of Weekly Work Hours in Canada - Newton, Keith; Leckie, Norm (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1979)
This paper is an attempt to shed some empirical light on the underlying determinants of the length of the work week.